2020
DOI: 10.1088/1361-665x/abb98c
|View full text |Cite
|
Sign up to set email alerts
|

A novel stick-slip piezoelectric rotary actuator designed by employing a centrosymmetric flexure hinge mechanism

Abstract: Although the stick-slip piezoelectric linear actuators have been widely investigated, the design of stick-slip piezoelectric rotary actuators is rarely reported and the corresponding output performances could be further improved. In this study, by employing a centrosymmetric flexure hinge mechanism, a novel stick-slip piezoelectric rotary actuator was designed. Its structure and working processes were addressed in detail, and the main structural parameters of the centrosymmetric flexure hinge mechanism were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The traditional stick-slip piezoelectric actuator has the problems of small stepping displacement, weak loading capacity, and large backward motion. Wang et al designed a right-angle triangular flexible mechanism [23], Huang et al designed a piezoelectric actuator with an L-type flexible mechanism [24] and Wang et al designed a viscous-slip piezoelectric actuator using a center-symmetric flexible mechanism [25], which were designed to optimize and improve the structure of mechanisms, so as to these studies were conducted to improve the drive performance of the piezo actuator by optimizing the mechanism structure. But there are problems such as large backward motion and low positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional stick-slip piezoelectric actuator has the problems of small stepping displacement, weak loading capacity, and large backward motion. Wang et al designed a right-angle triangular flexible mechanism [23], Huang et al designed a piezoelectric actuator with an L-type flexible mechanism [24] and Wang et al designed a viscous-slip piezoelectric actuator using a center-symmetric flexible mechanism [25], which were designed to optimize and improve the structure of mechanisms, so as to these studies were conducted to improve the drive performance of the piezo actuator by optimizing the mechanism structure. But there are problems such as large backward motion and low positioning accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement results showed that the maximum rotor speed was 0.153 rad/s around the x-axis and 0.154 rad/s around the y-axis at a 400 V voltage and 460 Hz frequency, respectively. In 2020, a stick-slip piezoelectric rotary actuator was designed by Wang et al [35]. The results showed that the maximum angular velocity of the actuator was about 55,000 µrad/s at the drive voltage of 100 V and the frequency of 600 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic drive motors are driven by elliptical friction under the action of applied ultrasonic voltage, with fast speed and self-locking characteristics of power failure, but they have high requirements for the drive signal and serious heating problems caused by friction and wear [3][4]. The stick-slip drive motors adopt an asymmetric drive wave (sawtooth wave signal), and utilize the difference between the maximum static friction and sliding friction to drive by inertia, with a simple principle of motion, compact structure, and a motion speed between the inchworm motors and ultrasonic motors [5][6][7][8]. As a result, stick-slip actuation is more advantageous than inchworm actuation and ultrasonic actuation, and has been widely used in areas such as precision instrument measurement, bioengineering, and micromanipulation.…”
Section: Introductionmentioning
confidence: 99%